Origin of the x-ray-absorption fine structure in photon-stimulated ion desorption from Si-adsorbate systems - MC GOVERN, IGNATIUS (My University, 1992)
There is no general agreement on whether photon-stimulated ion desorption (PSID) extended and near-edge x-ray-absorption fine structure (EXAFS and NEXAFS) can provide surface structural information. To address this question, we have monitored the H+-ion yield from Si(100)2?1-H, Si(111)7?7-H2O, and Si(111)7?7-H at the substrate Si K edge and the Cl+-ion yield for the systems Si(100)2?1-Cl and Si(111)7?7-Cl at both the substrate Si K edge and adsorbate Cl K edge. Moreover, we reassess our previously published Si K-edge H+-ion yield data from the Si(100)2?1-H2O system. The EXAFS in the ion yield spectra is analyzed with a view to clarifying the physical processes deter- mining the ion yield. At the substrate Si K edge, the similarity of near-neighbor distances and coordination numbers to bulk values in all the systems studied indicates that the ion yield at this edge is dominated by x-ray-induced electron-stimulated desorption. This is corroborated by NEXAFS data at the same absorption edge. For Si(100)2?1-Cl and Si(111)7?7-Cl the Cl+-ion yield at the Cl K edge produces EXAFS and NEXAFS spectra identical to those recorded using Auger-electron yield, indicating the likely desorption mechanism to be a Knotek-Feibelman intra-atomic Auger process. The implications of these findings for PSID EXAFS, and NEXAFS are discussed.
PUBLISHED
Keywords: Physics